Selective RAF inhibitor impairs ERK1/2 phosphorylation and growth in mutant NRAS, vemurafenib‐resistant melanoma cells. (8th April 2013) - Le, Kaitlyn; Blomain, Erik S.; Rodeck, Ulrich; Aplin, Andrew E.
Summary The RAF inhibitor vemurafenib achieves remarkable clinical responses in mutant BRAF melanoma patients. However, vemurafenib is burdened by acquired drug resistance and by the side effects associated with its paradoxical activation of the ERK1/2 pathway in wild‐type BRAF cells. This paradoxical effect has driven the development of a new class of RAF inhibitors. Here, we tested one of these selective, non‐paradox‐inducing RAF inhibitors termed paradox‐breaker‐04 (PB04) or PLX7904. Consistent with its design, PB04 is able to efficiently inhibit activation of ERK1/2 in mutant BRAF melanoma cells but does not hyperactivate ERK1/2 in mutant RAS‐expressing cells. Importantly, PB04 inhibited ERK1/2 phosphorylation in mutant BRAF melanoma cells with acquired resistance to vemurafenib/PLX4720 that is mediated by a secondary mutation in NRAS. Consistent with ERK1/2 reactivation driving the re‐acquisition of malignant properties, PB04 promoted apoptosis and inhibited entry into S phase and anchorage‐independent growth in mutant N‐RAS‐mediated vemurafenib‐resistant cells. These data indicate that paradox‐breaker RAF inhibitors may be clinically effective as a second‐line option in a cohort of acquired vemurafenib‐resistant patients.